2008
DOI: 10.1038/ejhg.2008.127
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypic analysis of tag SNPs of the interleukin-18 gene in relation to cardiovascular disease events: the MORGAM Project

Abstract: Interleukin-18 (IL-18) is a key inflammatory molecule suspected of being involved in the etiology of cardiovascular diseases (CVD). Five single nucleotide polymorphisms (SNPs) capturing the common genetic variation of the IL-18 gene (tag SNPs) were genotyped in five European prospective CVD cohorts including 1933 cases and 1938 non-cases as part of the MORGAM Project. Not a single SNP was found associated with CVD. However, a significant (P ¼ 0.002) gene-smoking interaction was observed. In smokers, the À105T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
0
11
0
1
Order By: Relevance
“…Future studies could also examine whether effect modifiers of any associations between IL-18 and CHD; previous studies have demonstrated interactions between IL-18 or IL-18 genotypes and factors related to CHD risk (e.g. metabolic syndrome [30], hypertension [45] or cigarette smoking [46]), any such interactions could change the predictive value of circulating IL-18 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could also examine whether effect modifiers of any associations between IL-18 and CHD; previous studies have demonstrated interactions between IL-18 or IL-18 genotypes and factors related to CHD risk (e.g. metabolic syndrome [30], hypertension [45] or cigarette smoking [46]), any such interactions could change the predictive value of circulating IL-18 levels.…”
Section: Discussionmentioning
confidence: 99%
“…15 Nonetheless, the level of evidence for the vast majority of currently suggested gene-smoking interactions ultimately remains very limited. The evolution of findings concerning an interaction between tobacco-smoking and variants in glutathione S-transferase genes with respect to cardiovascular disease risk-which started out as a seemingly plausible effect modification supported by multiple lines of evidence 8 and was further sugested later meta-analysis, 16 only to vanish with subsequent sample size escalation 17 -should be taken as a reminder of the danger of prematurely overinterpreting gene-smoking interactions or even higher order interactions (eg, gene-age-smoking).…”
Section: Breitlingmentioning
confidence: 99%
“…В другом, многоцентровом, исследовании Grisoni M.L. с соавторами [11] изучали вклад пяти полиморфных сайтов с однонуклеотидными заменами (SNP) в IL18R1, шести SNP в IL18RAP, и пяти SNP в IL18 и лиц, включенных в проект MORGAM с целью поиска вероятного взаимодействия между полиморфизмом генов комплекса сигнального пути ИЛ-18 и развитием инсультов (ишемических и геморрагических) и ИБС (включая установленный и возможный острый ИМ, коронарную смерть, нестабильную стенокардию и сердечную реваскуляризацию). Проект MORGAM основан на выборке 48 когорт из четырех регионов Европы.…”
Section: результатыunclassified